2018
DOI: 10.1111/1440-1681.12943
|View full text |Cite
|
Sign up to set email alerts
|

Activation of voltage‐gated sodium current and inhibition of erg‐mediated potassium current caused by telmisartan, an antagonist of angiotensin II type‐1 receptor, in HL‐1 atrial cardiomyocytes

Abstract: Telmisartan (TEL) is a non-peptide blocker of angiotensin II type-1 (AT ) receptor. However, the mechanisms through which this drug interacts directly with ion currents in hearts remain largely unclear. Herein, we aim to investigate the effects of TEL the on ionic currents and membrane potential of murine HL-1 cardiomyocytes. In whole-cell recordings, addition of TEL stimulated the peak and late components of voltage-gated Na currents (I ) with different potencies. The EC values required to achieve the stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 52 publications
(139 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, in the continued presence of SSM (3 µM), the subsequent addition of either tefluthrin (10 µM) or telmisartan (10 µM) was effective in reversing the SSM-induced inhibition of peak I Na . [20,[30][31][32][33]. As shown in Figure 2, SSM or SesA, at a concentration of 3 μM, produced inhibitory effects on the peak amplitude of INa.…”
Section: Comparison Between Effects Of Ssm Sesa Ssm Plus Tefluthrinmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, in the continued presence of SSM (3 µM), the subsequent addition of either tefluthrin (10 µM) or telmisartan (10 µM) was effective in reversing the SSM-induced inhibition of peak I Na . [20,[30][31][32][33]. As shown in Figure 2, SSM or SesA, at a concentration of 3 μM, produced inhibitory effects on the peak amplitude of INa.…”
Section: Comparison Between Effects Of Ssm Sesa Ssm Plus Tefluthrinmentioning
confidence: 78%
“…In another experiment, we tested the effects of SSM, sesamolin (SesA), SSM plus tefluthrin, and SSM plus telmisartan on the peak amplitude of I Na responding to rapid membrane depolarization to −10 mV from a holding potential of −80 mV. Tefluthrin, a type I pyrethroid insecticide, and telmisartan, a blocker of angiotensin II receptors, were previously demonstrated to activate I Na directly and effectively [ 20 , 30 , 31 , 32 , 33 ]. As shown in Figure 2 , SSM or SesA, at a concentration of 3 μM, produced inhibitory effects on the peak amplitude of I Na .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that GL might prevent cardiac damage by decreasing the oxidative stress associated with myocardial injury [8]. We therefore also tested whether GTs exerts any effects on I h present in HL-1 heart cells [44,45]. These experiments were conducted in cells bathed in Ca 2+ -free Tyrode’s solution, and the downsloping ramp pulse from −52 to −162 mV with a duration of 1 sec was applied to evoke I h in these cells.…”
Section: Resultsmentioning
confidence: 99%
“…The I K(erg) has been previously reported to be linked to the regulation of HIF (17). We next tested whether roxadustat can modify another type of K + current (i.e., I K(erg) ) which is inherently present in GH 3 cells [40,41,42]. These experiments were conducted in cells bathed in high-K + , Ca 2+ -free solution, and we filled the recording pipette with K + -containing solution.…”
Section: Resultsmentioning
confidence: 99%